Kejadian Wasting pada Balita Usia 6-59 Bulan: Wasting Incidence among Toddlers aged 6-59 Months - Erika, Erika; Sari, Yulia; Hajrah, Wa Ode (Jurnal Bidan Cerdas, 2020)
Wasting is an acute malnutrition which could indirectly increase infant mortality and morbidity. Currently, wasting was serious public health problem in Indonesia with 11,1% of prevalence. This study aimed to determine the incidence of wasting in childrens aged 6-59 months in the working area of Puskesmas Kelurahan Penjaringan I, North Jakarta from March to April, 2019. The researcher measured antropometry of children to see nutritional status based on indicator of BB/TB. A case control method, as well as purposive and accidental sampling technique, was carried out in this study. As many as 60 respondents were divided into 2 groups (30 cases group and 30 control group). The data were analyzed by using chi square test and multiple logistic regression. Infectious disease history (p=0.031) and protein intake (p=0.024) were associated with wasting incidence in children. Infectious diseases history was dominant factor determining of wasting in children aged 6-59 months in Puskesmas Kelurahan Penjaringan I, North Jakarta (OR=11.897; 95% CI=1.246-113.570). Fostering integrated health post by providing counseling about increasing nutrient intake especially protein intake and handling infectious diseases in children so that wasting can be handled properly.